The survivalist [videorecording (DVD)] - Rhys-Meyers, Jonathan, 1977-; Modine, Ruby, 1990-; Green, Jenna Leigh; Malkovich, John (Quiver Distribution, 2021)
After a viral pandemic decimates the world, a survivalist is forced to take on a group of heavily armed religious fanatics who believe that he is harboring a woman who could be the key to ending the virus and repopulating the world.